How globalization is changing our workforce: a global vision to job development. - Hafner D; Owens LA (Journal of Vocational Rehabilitation, 2008)
The field of supported employment has changed over the past twenty years. Unfortunately, job developers continue to struggle with ways in which we can assist individuals with disabilities reach their career goals. Many jobs are being sent oversees while even more are being replaced by technology. This manuscript addresses the need for employment professionals in the disability community to look beyond the traditional job market and look more globally.